Legal Protection for Children as Victims of Domestic Violence - Ismaidar Ismaidar; Rahmayanti Rahmayanti (Randwick International of Social Science Journal, 2023)
Domestic violence often occurs in human life. The forms of violence experienced by victims vary, both in the economic, social and educational fields.The formulation of the problem is how to protect children as victims of law (domestic violence). Victims who experience domestic violence are generally women and children. In this case, the government provides health facilities and efforts for children who have experienced violence in order to relieve the trauma experienced. This can be too contained in Law no. 23 of 2002 concerning Child Protection which has stipulated criminal sanctions, within the form of detainment or with. Which is for the good thing about the child. Legitimate security for children as casualties of residential viciousness is the assurance given, counting: providing legal help; privacy of the victim's personality; capture the culprit with preparatory prove; giving other help within the shape of wellbeing administrations; recovery endeavors. The reason of this investigate is to discover outlegal assurance for children as casualties (Household Savagery (KDRT) and lawful cures against children as victims of Domestic Violence (KDRT).This research uses descriptive analytical research method, the approach used is normative juridical. The approach method used in this research is the statutory approach.